Impact of Workplace Spirituality on Employee Productivity in Nepalese Hospitality Organizations - Biswakarma, Gangaram (Journal of Tourism and Hospitality Education, 2018)
In a rapidly changing and competitive world, managing an organization is becoming very complex. It is utmost vital to gain a competitive advantage by an organisation to survive the cut-throat competition. Hospitality organizations is one of them. Uniquely, these organizations can strengthen and improve its human resource productivity to gain competitive advantage. One of the element that influence productivity of employee is, how they are guided, mentored and supported in the organization and provided with workplace spirituality to contribute more effective in the organizational work process. Therefore, this research study aimed at analyzing the relationship between creating workplace spirituality, and how it influences the employee productivity in Nepalese hospitality organization. A sample of 150 employees from hospitality organizations was selected for the study with convenience sampling method. The study concluded that there is a positive relationship between workplace spirituality and productivity and workplace spirituality positively predict employee productivity in hospitality organization. This suggests that the workplace spirituality plays an important role to make the employee productive and satisfied. Employee thus become more productive over the long run compared with employees in organizations where spirituality is ignored or disrespected. Therefore, hospitality organizations should emphasize to make their respective organization spiritual and adopt spiritual environment, and also emphasize spiritual leadership. Journal of Tourism and Hospitality Education 8 (2018) Page: 62-76